Closed loop stepping motor application in prosthetics - Williams, K. F. (Cranfield University, 1969)
In recent years much work has been done in many countries on the development of powered artificial limbs for use by adults and children with congenital deficiencies i.e. present at birth, and by amputees. The established methods of actuating these powered limbs are either by pneumatic motors, operated from compressed carbon dioxide or by electric motors. Some designs have also used hydraulic and electro-hydraulic actuators. In the development of the complete powered limb the following problems have also to be considered: (a). The design of the mechanical components and the harness for attaching the appliance to the body. (b). Control input units by means of which signals from the wearer operate the powered limb. Control input signals maybe either mechanical (bone movement) or electrical. (c). The control system mechanies, involving the type of feedback which should be used. This can be either visual feedback or sensory feedback from the forces exerted by the appliance.